1112. #EducationInTheTimeofCOVID: Using Twitter to Disseminate Evidence-Based Medicine during a Pandemic. (31st December 2020) - Coleman, Caroline G; Daugherty, Timothy T; Chung, Yooree G; Xiao, Angel X; Sherman, Amy C; Axell-House, Dierdre B; Weatherhead, Jill E; Woc-Colburn, Laila; Chida, Natasha; Chida, Natasha; Jennifer, Spicer O
Abstract: Background: The medical community has used Twitter as a learning tool during the COVID-19 pandemic to digest the high volume of rapidly evolving literature. However, Twitter contains educational content of varying quality and accuracy. To address this issue, we created and disseminated visual abstracts of COVID-19 literature on Twitter to educate health professionals. Methods: Fellows and faculty members from multiple institutions collaborated with Emory University medical students to create visual abstracts of published COVID-19 literature (Figure 1). ID fellows and faculty identified and summarized 10-15 high-impact COVID-19 articles each week. Medical students created visual abstracts for each article, which fellows or faculty reviewed for accuracy. We disseminated them on Twitter (@JenniferSpicer4, 4, 373 followers) and our website (Figure 2). We measured engagement with tweets using Twitter Analytics. Figure 1: COVID-19 Visual Abstract Example Figure 2: Website hosting COVID-19 weekly literature summaries and visual abstracts (https://med.emory.edu/departments/medicine/divisions/infectious-diseases/covid19-roundup/ ) Results: Since March 2020, we have created, reviewed, and disseminated 139 graphics with 116 student authors and 33 fellow/faculty reviewers across three academic institutions (Table 1). Topics included public health & prevention, virology & basic science, epidemiology, transmission & infection control, clinical syndrome, diagnostics, therapeutics, vaccinology, and ethics & policy. Tweets had a median of 9, 300 impressions (interquartile range [IQR] 5, 432-13, 233) with 766 engagements (IQR 432-1, 288) and an engagement rate of 8.6% (IQR 7.1%-10.0%) (Table 2). Each tweet had a median of 25 retweets (IQR 17-38) and 55 likes (IQR 34-81). A few tweets had significantly higher metrics; maximum values were 84, 257 impressions, 9, 758 engagements, 19.0% engagement rate, 239 retweets, and 381 likes. In addition to disseminating graphics on Twitter, we received requests to use them as teaching aids from multiple health professionals worldwide, and the visual abstracts have been translated into Spanish and disseminated on Twitter and Instagram via @MEdSinFrontera. Table 1: Descriptive Statistics of COVID-19 Visual Series Table 2: Twitter Metrics for COVID-19 Visual Series (as of 6/10/2020) Conclusion: Engagement rates with our visual abstracts were high, demonstrating the power of Twitter. ID educators can use visual abstracts to summarize and disseminate accurate information to a large audience on social media, which is especially important in the setting of an emerging infection. Disclosures: All Authors : No reported disclosures